Ghost world - Clowes, Daniel; Grano, Adam.; Clowes, Daniel; Zwigoff, Terry (Seattle, Wash. Fantagraphics Books, 2008)
One of the best-selling and critically-acclaimed graphic novels of all-time telling the story of two supremely ironic, above-it-all teenagers facing the thrilling uncertainty of life after high school. As they attempt to carry their life-long friendship into a new era, the careful dynamics of their inseparable bond are jolted, and what seemed like a future of endless possibilities looks more like an encroaching reality of strip malls, low-paying service jobs and fading memories.
Includes screenplay by Daniel Clowes and Terry Zwigoff, for the film released in 2001, as well as additional drawings, cover art, etc.
UCWS-2014-G-1666 donated by Mr. Ronald Salamat
Keywords: Young women -- United States -- Comic books, strips, etc; Female friendship -- Comic books, strips, etc; City and town life -- United States -- Comic books, strips, etc; Comic books, strips, etc; Graphic novels